PERAN DINAS SOSIAL KOTA PEKANBARU TERHADAP LADY BOY (WARIA) DI KOTA PEKANBARU - Dani, Egi Dwi Rahmat; Zahirman, Zahirman; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the role of the Pekanbaru City Social Service against Lady Boy in Pekanbaru City. The formulation of the problem in this study is How the role of the Pekanbaru Social Service against Lady Boy in Pekanbaru City. This research uses a qualitative approach. The informants in this study were the Section Head of Social Tuna Rehabilitation, Victims of Violence and Trafficking in Persons at the Social Service City of Pekanbaru. Data collection techniques are carried out through observation, interviews and documentation. Data analysis techniques using data collection, data reduction, data presentation, and conclusions. Based on the results of research conducted, it can be concluded that the Role of the Social Service of the City of Pekanbaru Against Lady Boy in Pekanbaru City has generally played a role, but has not been realized as a whole due to budget allocations.Key Words: Social Service, Lady Boy